2011
DOI: 10.3892/ijmm.2011.813
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a novel alkaline serine protease secreted by Vibrio metschnikovii

Abstract: Abstract.A novel extracellular alkaline serine protease secreted by Vibrio metschnikovii (V. metschnikovii) ATCC700040 cells was purified by three chromatographic steps and characterized in terms of enzymatic kinetics and substrate specificity. The purified enzyme (named AKP-Vm) was composed of a single polypeptide with an apparent molecular weight of 50 kDa on 12% SDS-polyacrylamide gel in the presence of CuCl 2 . The optimal temperature and the pH for the enzyme were found to be 37˚C and 9.5, respectively. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Generally, the molecular masses of alkaline proteases from microorganisms ranged from 15 to 30 kDa (Deng et al 2010;Joshi and Satyanarayana 2013;Raval et al 2014;Gohel and Singh 2015) with few exceptions. For example, alkaline protease reported from Vibrio metschnikovii ATCC700040 had a molecular weight of 50 kDa (Park et al 2012), and that from Stenotrophomonas maltophilia had a molecular weight of 98 kDa (Waghmare et al 2015).…”
Section: Purification Of Alkaline Proteasementioning
confidence: 99%
“…Generally, the molecular masses of alkaline proteases from microorganisms ranged from 15 to 30 kDa (Deng et al 2010;Joshi and Satyanarayana 2013;Raval et al 2014;Gohel and Singh 2015) with few exceptions. For example, alkaline protease reported from Vibrio metschnikovii ATCC700040 had a molecular weight of 50 kDa (Park et al 2012), and that from Stenotrophomonas maltophilia had a molecular weight of 98 kDa (Waghmare et al 2015).…”
Section: Purification Of Alkaline Proteasementioning
confidence: 99%
“…Some studies propose that metal ions like Na + , K + , and Ca 2+ can activate these fibrinolytic enzymes [ 65 , 66 ]. While numerous papers have examined the impact of metal ions on crude protease extracts from different sources, only a handful of authors have successfully isolated pure forms of fibrinolytic enzymes [ 52 , 54 , 67 , 68 , 69 ]. In this present study, the stability of the fibrinolytic enzyme was tested by treating it with different metal ions and it was concluded that the enzyme activity was significantly altered by these metal ions.…”
Section: Discussionmentioning
confidence: 99%